A Systematic Review Of The Factors Influencing Successful Vaginal Birth After Cesarean - Fatimah Azzahra; Sri Endah Rahayuningsih; Anita Rachmawati; QORINAH ESTININGTYAS SAKILAH ADNANI; VICTOR ABIOLA ADEPOJU (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Background: This systematic review explores factors influencing the success of Vaginal Birth After Cesarean (VBAC) in response to increasing global cesarean rates. VBAC reduces the need for repeat cesareans and associated risks. Purpose: To identify key medical, psychological, and institutional factors affecting VBAC outcomes. Methods: A total of 21 studies were reviewed from PubMed, ScienceDirect, and Google Scholar using PRISMA-ScR criteria. The analysis focused on maternal age, previous vaginal birth, cervical dilatation, healthcare access, and psychosocial support. Results: Successful VBAC was linked to younger maternal age, prior vaginal birth experience, spontaneous labor onset, and adequate cervical dilatation at admission. Psychosocial support, including family encouragement and professional guidance, significantly influenced VBAC decisions. Hospital policies promoting VBAC and ensuring access to emergency services further enhanced success rates. Conclusion: Medical, social, and institutional factors significantly affect VBAC success. Establishing standardized guidelines and providing improved counseling are essential to support women’s choices during childbirth. Future research should focus on large, diverse populations to confirm predictors and assess long-term outcomes compared to repeat cesareans.